An Online Ballistics Imaging System for Firearm Identification - Huang, Zhihu (2010)
Since the traditional ballistics imaging system is dependent upon the expertise and experience of end-user, an intelligent ballistics imaging system is highly demanded to overcome the drawbacks of traditional techniques. This paper aims to develop a novel ballistics imaging system so as to combine the traditional functions with new features such as the line-scan image module, the characteristics extraction module, and the intelligent image processing module. With the help of these features, the new system can identify firearm more efficiently and effectively than the traditional techniques